Emerging knowledge - intensive industries in the process of formulating industrial development policies of some countries around the world - Nguyen Nam Hai, (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Along with the strong development of science and technology, the knowledge economy has become a general development trend of the world economy and has been chosen by many countries around the world as a development strategy. In the context of the Fourth Industrial Revolution (Industry 4.0) taking place strongly world-wide nowadays, the world economy has entered the stage of the knowledge economy. Therefore, many countries and territories have succeeded in identifying and making robust policies supporting the emerging knowledge-intensive industries to make breakthrough, such as Japan, Korea, and Taiwan. For Vietnam, the Party and State have identified science and technology as the driving force for the country's development. Therefore, the knowledge-intensive industry will be the main driver of sustainable economic growth. This article will clarify the concept of the role and the status of identifying a number of emerging knowledge-intensive industries in the process of formulating industrial development policies of countries around the world, thereby, as a basis. to propose appropriate plans to identify a number of emerging knowledge-intensive industries in the process of industrial policy formulation in Vietnam in the coming time. Code: 22080301